AN ESTIMATION OF PER CAPITA FOOD CONSUMPTION AND RELATED POVERTY IN FAQIRABAD AREA (PESHAWAR CITY) - Gul, Aliya; Karim, Robina; Nasrullah; Osaidullah (European Scientific Journal, ESJ, 2014)
This study analyzes the per capita food consumption and related poverty in Peshawar Valley, Faqirabad Area was selected. The average household size, based on 400 households is 7.77. It appears that on average an adult equivalent takes 210.30 grams of flour, 73.10 grams of meat, 57.11 grams of rice, 319.14 grams of vegetables, 52.30 grams of pulses, 193.00 grams of fruits, 191.71 grams of milk, 51.80 grams of fats, 8.65 grams of black tea, 39.56 grams of sugar, and 6.16 grams of spices daily. To live a normal life an adult person requires 2350 calories per day. The poverty status of the households surveyed shows that out of 400 households studied, 58.5% are above, 37% below, and 4.5% on the poverty line The comparison shows that in most of the cases, food consumption has reduced due to price hike, so it is recommended that actions should be taken to either stabilize the prices by subsidizing the major food items or to increase the monthly incomes of households to help them increase food consumption.